Participation in the International Judo Federation World Tour competitions and performance in Tokyo Olympic Games - Santos, D. F.; Kons, R. L.; Lopes-Silva, J. P.; Agostinho, M. F.; Detanico, D.; Takito, M. Y.; Franchini, E. (Frontiers in Sports and Active Living, 2023)
Introduction: The International Judo Federation introduced a ranking system in 2009 that determines top athletes for the Olympic Games and seeds them in competitions. Previous research indicated that this ranking list and past performances predicted 19%-27% of performance in the Olympic Games and World Championships. However, due to the COVID-19 pandemic, the relationship between Judo World Tour competitions and Olympic Games performance may have been affected. This study aimed to examine the relationship between athletes' performance in Judo World Tour competitions and their competitive performance at the Olympic Games.